2021
DOI: 10.1016/j.isci.2021.103509
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine inhibits the mitochondrial antioxidant system in activated T cells

Abstract: HighlightsHCQ inhibits proliferation of human CD4 T-cells without affecting early activation HCQ dysregulates mitochondrial superoxide production in activated CD4 T-cells Dysregulated ROS impairs autophagic flux in activated CD4 T-cells HCQ limits antigenspecific T cell responses in patients with celiac disease ex vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…As mentioned above, the autophagosome was first formed to encapsulate the damaged organelles and proteins caused by PTT/PDT at the beginning of the autophagy process and then fused with lysosomes and was further degraded for positive cellular metabolism. HCQ could inhibit the autophagy process through disrupting the fusion between autophagosome and lysosome, thus causing the aggregation of cellular metabolic waste and cell death. Therefore, detecting the content of autophagosomes plays a key role in evaluating the autophagy behaviors induced by PDT and the autophagy inhibiting effect of HCQ. Herein, we observed the autophagosome content in CAL-27 cells after various treatments using confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the autophagosome was first formed to encapsulate the damaged organelles and proteins caused by PTT/PDT at the beginning of the autophagy process and then fused with lysosomes and was further degraded for positive cellular metabolism. HCQ could inhibit the autophagy process through disrupting the fusion between autophagosome and lysosome, thus causing the aggregation of cellular metabolic waste and cell death. Therefore, detecting the content of autophagosomes plays a key role in evaluating the autophagy behaviors induced by PDT and the autophagy inhibiting effect of HCQ. Herein, we observed the autophagosome content in CAL-27 cells after various treatments using confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…HCQ-induced autophagy dysfunction has been attributed to apoptotic cell death, particularly in pancreatic cancer cells and effector CD4 T cells 9,40,41 . We recently reported that autophagy dysfunction caused by HCQ is associated with reduced proliferation of activated CD4 T cells 42 . This effect was due to disruption of the mitochondrial antioxidant system and was reversed by the antioxidant N-acetyl cysteine (NAC).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of autophagy can relieve the development of RA. Kim et al reported that the administration of hydroxychloroquine, a drug used to treat patients with RA, in PBMC-derived human CD4 + T cells inhibits autophagic flux by interfering with mitochondrial superoxide production and induces excessive ROS, thereby inhibiting the proliferation of activated CD4 + T cells ( Kim et al, 2021 ). According to van Loosdregt et al, the administration of hydroxychloroquine in PBMC-derived human CD4 + T cells increases apoptotic CD4 + T cells, suggesting hydroxychloroquine improves joint inflammation by reducing auto-reactive T cells ( Van Loosdregt et al, 2013 ).…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%